The Diamond Pipeline into the Third Millennium: A Multi-channel System from the Mine to the Consumer - Sevdermish, M.; Miciak, A.; Levinson, A. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1998)
Summary The single-channel marketing system for rough diamonds, presented by DeBeers as the ideal since the mid 1930s, has lost market share in the past decade. Most diamond industry analyst snow recognize the diamond pipeline to consist of two marketing channels (tiers) for rough diamonds; one for better-quality and the other for lower-quality, rough diamonds. However, we suggest that the pipeline now consists of three distinct channels that extend from the mine {rough diamonds) to the consumer (polished diamonds): 1 ) the Traditional Gem Channel, whose stability and prosperity are maintained by De Beers and which is characterized by high-value diamonds; 2) the Indian Channel, a high-volume market based on small, low-quality diamonds cut in India, most of which were formerly considered industrial diamonds; and 3) the Russian Channel, whose status and potential have yet to be fully determined. Each channel has its own characteristic organization and distribution system.These developments bode well for the fledgling Canadian diamond industry, as they indicate that Canadian diamond producers will have choices for marketing their rough diamonds.